TRAIL signals through the ubiquitin ligase MID1 to promote pulmonary fibrosis - Adam M. Collison; Junyao Li; Ana Pereira de Siqueira; Xuejiao Lv; Hamish D. Toop; Jonathan C. Morris; Malcolm R. Starkey; Philip M. Hansbro; Jie Zhang; Joerg Mattes (BMC Pulmonary Medicine, 2019)
Abstract Background Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) has previously been demonstrated to play a pro-inflammatory role in allergic airways disease and COPD through the upregulation of the E3 ubiquitin ligase MID1 and the subsequent deactivation of protein phosphatase 2A (PP2A). Methods Biopsies were taken from eight IPF patients presenting to the Second Affiliated Hospital of Jilin University, China between January 2013 and February 2014 with control samples obtained from resected lung cancers. Serum TRAIL, MID1 protein and PP2A activity in biopsies, and patients’ lung function were measured. Wild type and TRAIL deficient Tnfsf10 −/− BALB/c mice were administered bleomycin to induce fibrosis and some groups were treated with the FTY720 analogue AAL(s) to activate PP2A. Mouse fibroblasts were treated with recombinant TRAIL and fibrotic responses were assessed. Results TRAIL in serum and MID1 protein levels in biopsies from IPF patients were increased compared to controls. MID1 levels were inversely associated while PP2A activity levels correlated with DLco. Tnfsf10 −/− and mice treated with the PP2A activator AAL(s) were largely protected against bleomycin-induced reductions in lung function and fibrotic changes. Addition of recombinant TRAIL to mouse fibroblasts in-vitro increased collagen production which was reversed by PP2A activation with AAL(s). Conclusion TRAIL signalling through MID1 deactivates PP2A and promotes fibrosis with corresponding lung function decline. This may provide novel therapeutic targets for IPF.